Using maleic anhydride functionalized graphene oxide for improving the interfacial properties of carbon fiber/BMI composites - W. Li; Y. Z. Yue; M. Y. Wang; Q. Li; R. Ren (eXPRESS Polymer Letters)
Maleic anhydride functionalized graphene oxide (MAH-GO) was synthesized and then introduced into carbon fiber (CF) reinforced bismaleimide (BMI) composites, with the aim of improving the interfacial adhesion strength between CF and BMI resin. Various characterization techniques including Fourier transform infrared spectroscopy (FT-IR), X-ray photoelectron spectra (XPS) and thermogravimetric analysis (TGA) demonstrated that the maleic anhydride has been successfully grafted onto the GO surfaces. The study showed that the interlaminar shear strength (ILSS) and flexural properties of CF/BMI composites were all improved by the incorporation of GO and MAH-GO, and the MAH-GO showed the substantially improved effect due to the strong interaction between the MAH-GO and the resin matrix. The maximum increment of the ILSS, flexural strength and flexural modulus of composites were 24.4, 28.7 and 49.7%, respectively. Scanning electron microscope (SEM) photographs of the fracture surfaces revealed that the interfacial bonding between CF and resin matrix was significantly strengthened by the addition of MAH-GO. The results suggest that this feasible method may be an ideal substitute for the traditional method in the interfacial modification of composites.